2004
DOI: 10.1128/jvi.78.6.3149-3154.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell, but Not Long-Distance, Spread of RNA Silencing That Is Induced in Individual Epidermal Cells

Abstract: A Turnip crinkle virus (TCV)-based system was devised to discriminate cell-to-cell and systemic long-distance spread of RNA silencing in plants. Modified TCV-GFP⌬CP, constructed by replacing the coat protein (CP) gene with the green fluorescent protein (GFP) gene, replicated in single epidermal cells but failed to move from cell to cell in Nicotiana benthamiana. Mechanical inoculation of TCV-GFP⌬CP induced effective RNA silencing in single epidermal cells which spread from cell to cell to form silenced foci on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 41 publications
2
60
0
2
Order By: Relevance
“…It was shown that a short-distance spreading of RNA silencing, once initiated from a small group of cells, can extend over 10-15 cells independently of the presence of cognate transcripts (Himber et al, 2003). Short range silencing was observed for both transgenes and endogenous genes (Ryabov et al, 2004;Schwach et al, 2005;Kalantidis et al, 2006;Dunoyer et al, 2007;Smith et al, 2007).…”
Section: Short Range Silencingmentioning
confidence: 98%
“…It was shown that a short-distance spreading of RNA silencing, once initiated from a small group of cells, can extend over 10-15 cells independently of the presence of cognate transcripts (Himber et al, 2003). Short range silencing was observed for both transgenes and endogenous genes (Ryabov et al, 2004;Schwach et al, 2005;Kalantidis et al, 2006;Dunoyer et al, 2007;Smith et al, 2007).…”
Section: Short Range Silencingmentioning
confidence: 98%
“…Firstly, Fny-CMVD2b might induce highly localized, non-systemic RNA silencing against homologous sequences in the challenging virus. Highly localized RNA silencing can be induced by viral mutants lacking the gene for a silencing suppressor protein; for example, a P38 (a CP) deletion mutant of tobacco crinkle virus (Ryabov et al, 2004). Highly localized RNA silencing, without detectable accumulation of siRNAs, can also occur in certain lines of transgenic plants overexpressing the gfp reporter gene (Kalantidis et al, 2006).…”
Section: Cross-protection By Cmvd2bmentioning
confidence: 99%
“…We previously developed a Turnip Crinkle Virus (TCV)-based local silencing assay to investigate intraand intercellular VIGS in Nicotiana benthamiana (Qin et al, 2012;Ryabov et al, 2004;Shi et al, 2009;Zhou et al, 2008). TCV belongs to Carmovirus with a single positive-stranded RNA genome (Carrington et al, 1989).…”
Section: Rna Silencing Is An Innate Antiviral Mechanism Conserved In mentioning
confidence: 99%